Steady/transient state spectral researches on the solvent-triggered and photo-induced novel properties of metal-coordinated phthalocyanines. Issue 10 (17th February 2022) - Cao, Hongyu; Gong, Meina; Wang, Mengyan; Tang, Qian; Wang, Lihao; Zheng, Xuefang
Abstract : The large conjugated system and the d orbitals of metallic phthalocyanines (MPcs) are easily triggered by solvent molecules and light to cause variations in photo-physical and photo-chemical properties. Abstract : The large conjugated system and the d orbitals of metallic phthalocyanines (MPcs) are easily triggered by solvent molecules and light to cause variations in photo-physical and photo-chemical properties. To clarify the novel properties of photo-excited MPcs in solvents, the steady/transient state spectral data were collected to investigate four MPc templates, including FePc, ZnPc, CoPc and AlClPc. The Q bands of FePc and CoPc were prone to redshift, while the peaks of ZnPc and AlClPc tended to blueshift in various solvents compared with that in DMSO. With xenon lamp irradiation, the characteristic absorption peak intensity of FePc and ZnPc in DMSO decreased gradually and then increased after being subjected to dark condition. The transient absorption spectra and kinetic data illustrated that photo-excited FePc and CoPc produced relatively short lifetime transient intermediates. The positive absorption at 650 nm in the Q bands of FePc and CoPc could be assigned to the d–π* electron transition in transient intermediates with unpaired d-orbital electron in the open shell configuration of Fe 2+ and Co 2+ . The above studies were of great significance for the application of solvent-triggered and photo-induced novel properties of MPcs.